Liquid Phase Exfoliation, characterization, and printing of SnSe and PtSe2 devices - Fabiano, Noemi (Trinity College Dublin. School of Chemistry. Discipline of Chemistry, 2024)
The demand for optical-to-electrical and/or electrical-to-optical transducers is growing exponentially as optics are increasingly adopted for energy-efficient data transmission. Displays and light sensors are increasingly being integrated in ever more everyday objects. Indeed, optoelectronics is at the core of countless science disciplines and technological applications and there is a clear roadmap towards achieving not only broader band, faster and higher sensitivity (or brighter) devices, but also to develop devices with new functionalities. Since 2010-2011, the relatively young field of two-dimensional materials has experienced a new interest, originating from the research on graphene, and other related atomically thin 2D semiconductors. Recent breakthroughs have shown these 2D materials to cover a broader bandwidth range in the electromagnetic spectrum. This is due to their unique property of encompassing large exciton binding energies and exceptionally strong light-matter interaction. This makes 2D semiconductors extremely appealing for optoelectronic applications where conventional semiconductors cannot provide the same performance nor added functionality. Due to the increasing demand for energy and the ongoing climate crisis, it is crucial to develop sustainable materials, and devices able to produce and store solar energy and exploit sustainable processes like hydrogen evolution. Current sustainable devices, such as solar cells and heterojunctions, can be improved with the addition of 2D materials. This work studies the properties of two materials, SnSe and PtSe2, for applications in optoelectronic devices. SnSe has demonstrated versatility in thermoelectronics, photodetectors, solar cells, photocatalysts, phase change memory, and gas sensors. The indirect bandgap of SnSe is 0.9 eV, and the direct is 1.3 eV. Our interest towards PtSe2 grew due to its photonic, physical, and chemical properties. The exfoliation of PtSe2 allows us to modulate the electronic structure, resulting in a tuneable bandgap, which allows a transition from semimetal to semiconductor when exfoliated to less than three layers, with a monolayer bandgap of 1.17 eV. Liquid Phase Exfoliation (LPE) is versatile, scalable, and sustainable and allows processes that would be impossible otherwise. This technique can obtain free-standing films, facilitating nanomaterial mixing to form heterostructured solids and enabling insertion in a polymer matrix. In this work, LPE methodologies are developed for the exfoliation of both SnSe and PtSe2. The obtained dispersions were characterized with UV-Vis, SEM, TEM, and AFM. These dispersions were then printed on a substrate and the obtained device underwent photoelectrical characterization with current-voltage, photo response and power dependence studies.
APPROVED
Keywords: exfoliation; tin selenide; platinum selenide; printing